Development of a reactor with carbon catalysts for modular-scale, low-cost electrochemical generation of H2O2. Issue 2 (1st March 2017) - Chen, Zhihua; Chen, Shucheng; Siahrostami, Samira; Chakthranont, Pongkarn; Hahn, Christopher; Nordlund, Dennis; Dimosthenis, Sokaras; Nørskov, Jens K.; Bao, Zhenan; Jaramillo, Thomas F.
Abstract : Small-scale reactors for H2 O2 production that can couple to renewable energy sources would be of great benefit for decentralized water purification. Abstract : The development of small-scale, decentralized reactors for H2 O2 production that can couple to renewable energy sources would be of great benefit, particularly for water purification in the developing world. Herein, we describe our efforts to develop electrochemical reactors for H2 O2 generation with high Faradaic efficiencies of >90%, requiring cell voltages of only ∼1.6 V. The reactor employs a carbon-based catalyst that demonstrates excellent performance for H2 O2 production under alkaline conditions, as demonstrated by fundamental studies involving rotating-ring disk electrode methods. The low-cost, membrane-free reactor design represents a step towards a continuous, modular-scale, de-centralized production of H2 O2 .